2018
DOI: 10.1038/s41598-018-35710-y
|View full text |Cite
|
Sign up to set email alerts
|

BST-2 promotes survival in circulation and pulmonary metastatic seeding of breast cancer cells

Abstract: Bone marrow stromal antigen 2 (BST-2) mediates various facets of cancer progression and metastasis. Here, we show that BST-2 is linked to poor survival in invasive breast cancer patients as its expression positively correlates with disease severity. However, the mechanisms that drive the pro‐metastatic functions of BST-2 are not fully understood. Correlation of BST-2 expression and tumor aggressiveness was analyzed in human tissue samples. Migration, invasion, and competitive experimental metastasis assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
(80 reference statements)
1
20
1
Order By: Relevance
“…In addition, it has been suggested that increased immune cell adhesion and resistance of cancer cells to tamoxifen-induced apoptosis is linked to BST-2 expression [27,28,30]. We have also shown that the silencing of BST-2 in murine and human breast cancer cell lines results in a shift from a highly aggressive to a non-aggressive phenotype, including loss of cell to cell and cell to ECM adhesion [24,29], decrease in anchorage-independent growth/survival, formation of invadopodia for ECM remodeling, migration, and invasion [31]. Together, these findings suggest a potential for BST-2 as a valuable therapeutic target.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, it has been suggested that increased immune cell adhesion and resistance of cancer cells to tamoxifen-induced apoptosis is linked to BST-2 expression [27,28,30]. We have also shown that the silencing of BST-2 in murine and human breast cancer cell lines results in a shift from a highly aggressive to a non-aggressive phenotype, including loss of cell to cell and cell to ECM adhesion [24,29], decrease in anchorage-independent growth/survival, formation of invadopodia for ECM remodeling, migration, and invasion [31]. Together, these findings suggest a potential for BST-2 as a valuable therapeutic target.…”
Section: Introductionmentioning
confidence: 83%
“…TAMs promote tumor cell invasion and consequently tumor progression [31]. They also secrete interferon molecules (IFN) that induce overexpression of bone marrow stromal antigen 2 (BST-2), a type II transmembrane protein that supports metastasis formation by mediating CTC survival, invasion, and dissemination [33]. Overall, CTC dynamic state between epithelial or mesenchymal states [1,29] and the heterotypic interactions among the different cell types within a cluster are critical for their survival and collective invasion [34].…”
Section: Are Single Ctcs or Ctc Clusters Involved In Metastasis Formamentioning
confidence: 99%
“…CTC clusters could be targeted with agents that exploit the presence of TAMs [31] and neutrophils [75] in such clusters (e.g., immune checkpoint blockade antibodies and targeting therapy). Moreover, TAM-derived IFNs induce BST-2 overexpression that supports metastasis formation [33]. In a mouse model of breast cancer, BST-2 silencing reduces CTC number and lung metastases [33].…”
Section: Ctc Targeting For Metastasis Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…3C). H3F3C is a novel unannotated gene that plays a role in maintaining nucleosome structure 33,34 while BST2 is associated with interferon gamma and other cytokine signaling pathways in the immune system 35,36 . Differentially expressed naked mole rat uTARs were also identified within neutrophils, T cells, and macrophages ( Fig.…”
Section: ____________________________________________________________mentioning
confidence: 99%